Question
upstudy study bank question image url

Question 16, 1.3.93 HW Score: 7 Points: Use the trigonometric function values of the quadrantal angles to evaluate the given expression. \[ 3\left(\csc 90^{\circ}\right)^{2}+5\left(\tan 180^{\circ}\right)^{2}+\sec 180^{\circ} \] \[ 3\left(\csc 90^{\circ}\right)^{2}+5\left(\tan 180^{\circ}\right)^{2}+\sec 180^{\circ}= \] \( \square \) (Simplity your answer, including any radicals. Use integers or fractions for any numbers in the expression.)

Ask by Johnston Chen. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\(2\)

Solution

To evaluate the expression: \[ 3\left(\csc 90^{\circ}\right)^{2} + 5\left(\tan 180^{\circ}\right)^{2} + \sec 180^{\circ} \] Let's break it down term by term: 1. **\(\csc 90^{\circ}\):** \[ \csc \theta = \frac{1}{\sin \theta} \] \[ \csc 90^{\circ} = \frac{1}{\sin 90^{\circ}} = \frac{1}{1} = 1 \] \[ \left(\csc 90^{\circ}\right)^2 = 1^2 = 1 \] \[ 3 \times 1 = 3 \] 2. **\(\tan 180^{\circ}\):** \[ \tan \theta = \frac{\sin \theta}{\cos \theta} \] \[ \tan 180^{\circ} = \frac{\sin 180^{\circ}}{\cos 180^{\circ}} = \frac{0}{-1} = 0 \] \[ \left(\tan 180^{\circ}\right)^2 = 0^2 = 0 \] \[ 5 \times 0 = 0 \] 3. **\(\sec 180^{\circ}\):** \[ \sec \theta = \frac{1}{\cos \theta} \] \[ \sec 180^{\circ} = \frac{1}{\cos 180^{\circ}} = \frac{1}{-1} = -1 \] Now, combine all the results: \[ 3 + 0 - 1 = 2 \] **Answer:** \(2\)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To evaluate the expression, we first need to recall the values of the trigonometric functions at the specified angles. 1. \(\csc 90^{\circ} = 1\) (since \(\sin 90^{\circ} = 1\)) 2. \(\tan 180^{\circ} = 0\) (since \(\sin 180^{\circ} = 0\) and \(\cos 180^{\circ} = -1\)) 3. \(\sec 180^{\circ} = -1\) (since \(\cos 180^{\circ} = -1\)) Now, we can substitute these values into the expression: \[ 3\left(\csc 90^{\circ}\right)^{2} + 5\left(\tan 180^{\circ}\right)^{2} + \sec 180^{\circ} \] \[ = 3(1)^{2} + 5(0)^{2} + (-1) \] \[ = 3(1) + 5(0) - 1 \] \[ = 3 + 0 - 1 \] \[ = 3 - 1 \] \[ = 2 \] Thus, the final answer is: \[ \boxed{2} \]

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy